Declining genetic polymorphism of the C-terminus Merozoite Surface Protein-1 amidst increased Plasmodium knowlesi transmission in Thailand - Parsakorn Tapaopong; Sittinont Chainarin; Abdulrohman Mala; Arnuwat Rannarong; Nikom Kangkasikorn; Teera Kusolsuk; Wanlapa Roobsoong; Liwang Cui; Wang Nguitragool; Jetsumon Sattabongkot; Sirasate Bantuchai (Malaria Journal, 2024)
Abstract Background Recent reports from Thailand reveal a substantial surge in Plasmodium knowlesi cases over the past decades, with a more than eightfold increase in incidence by 2023 compared to 2018. This study investigates temporal changes in genetic polymorphism associated with the escalating transmission of P. knowlesi malaria in Thailand over time using the prominent vaccine candidate, pkmsp1 as a marker. Methods Twenty-five P. knowlesi samples collected in 2018–2023 were sequenced for the 42-kDa region of pkmsp1 and compared with 24 retrieved sequences in 2000–2009, focusing on nucleotide diversity, natural selection, recombination rate, and population differentiation. Results Seven unique haplotypes were identified in recent samples, compared to 15 in earlier samples. Nucleotide and haplotype diversity were lower in recent samples (π = 0.016, Hd = 0.817) than in earlier samples (π = 0.018, Hd = 0.942). Significantly higher synonymous substitution rates were observed in both sample sets (dS–dN = 2.77 and 2.43, p < 0.05), indicating purifying selection and reduced genetic diversity over time. Additionally, 8 out of 17 mutation points were located on predicted B-cell epitopes, suggesting an adaptive response by the parasites to evade immune recognition. Population differentiation analysis using the fixation index (Fst) revealed high genetic differentiation between parasite populations in central and southern Thailand or Malaysia. Conversely, the relatively lower Fst value between southern Thailand and Malaysia suggests a closer genetic relationship, possibly reflecting historical gene flow. Conclusion This study highlights a decline in genetic diversity and evidence of purifying selection associated with the recently increased incidence of P. knowlesi malaria in Thailand. The minor genetic differentiation between P. knowlesi populations from southern Thailand and Malaysia suggests a shared recent ancestry of these parasites and underscores the need for coordinated efforts between the two countries for ...